Employee engagement at a higher education institution in South Africa: Individual, team and organisational levels. Issue 2 (4th March 2019) - Ndoro, Tinashe; Martins, Nico
Abstract : We examined the levels of employee engagement among staff members at a higher education institution in South Africa at the individual, team, and organisational levels. The participants ( N = 202) completed a validated measure of employee engagement (females = 62.4%; academic staff = 28.2%). Data analysis indicated that the highest level of employee engagement was at the team level. The lowest level of employee engagement was at the individual level. Findings suggest a need for interventions to increase employee engagement at the individual level, in order to allow for the comprehensive implementation of mission aligned strategies at higher education institutions.